Analisis Confirmatory Faktor Pembentuk Suksesi Family Bisnis UMKM di Kota Payakumbuh - Hikmil Kumala; Yulhendri Yulhendri (Jurnal Ecogen, 2023)
The study aims to analyze how the influence of succession on the sustainability of family businesses in Payakumbuh City. This type of research is a quantitative descriptive study that uses primary and secondary data with data sources coming from people who have family businesses in Payakumbuh City. The analytical method used is Confirmatory Factor Analysis (CFA).The results of the analysis show that the social responsibility variable has no significant effect on the sustainability of the family business in Payakumbuh city. The succession variable has no significant effect on the sustainability of the family business in Payakumbuh. This happens because the sample in this study is still a lot of family businesses or new SMEs in Payakumbuh City.